COVID-19, an Opportunity for Developing Countries? - Smith, Lee; Veronese, Nicola; Racalbuto, Vincenzo; Pizzol, Damiano (Frontiers in Public Health, 2020)
The COVID-19 outbreak was declared by the World Health Organization (WHO) as global pandemic in March 2020. Considering the necessity to implement rapid response to control the pandemic and the fragility and the state of need of low income countries, it will be mandatory to develop a global approach in order to reduce the spread of infection and the creation of community viral reservoirs. So far, we could hypothesize a worst case scenario in which when the COVID-19 outbreak hits a peak in Africa and in low-income countries, the majority of such countries will be unprepared, with low resources allocated for affording the viral emergency and the consequences will be catastrophic with no lesson learnt. In the best case scenario, the COVID-19 will not affect Africa or South America on a large scale and, if the prevention measures will be implemented, we could register a lower incidence of hygiene linked diseases that still represent leading causes of death.